2022
DOI: 10.1186/s12884-022-04880-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of place birth: a multinomial logistic regression and spatial analysis of the Ethiopian mini demographic and health survey data, 2019

Abstract: Background Maternal and neonatal health significantly improves when birth is attended at health institutions where there are quality services and skilled attendants. In contrary, home birth results in high rates of maternal and neonatal mortality. Thus, this study aimed to determine the spatial distribution of home birth and to identify determinants of place of birth in Ethiopia based on the recent national survey. Methods Ethiopian mini-DHS-2019 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Likewise, the odds of IDD among women from LMICs were 7.05 and 5.57, respectively, compared to women from upper-middle income countries. Such strong association between wealth/income and IDD was consistent with previous studies from different LMICs [ 13 , 14 , 16 , 21 , 22 , 25 , 41 , 44 , 51 ]. The observed wealth–health correlation in terms of the choice of place of delivery among the rich and the poor could possibly be attributed to financial need to access and use healthcare resources in general.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, the odds of IDD among women from LMICs were 7.05 and 5.57, respectively, compared to women from upper-middle income countries. Such strong association between wealth/income and IDD was consistent with previous studies from different LMICs [ 13 , 14 , 16 , 21 , 22 , 25 , 41 , 44 , 51 ]. The observed wealth–health correlation in terms of the choice of place of delivery among the rich and the poor could possibly be attributed to financial need to access and use healthcare resources in general.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the odds of IDD were higher among women who had no media exposure compared to their counterparts. This finding was parallel to different studies conducted elsewhere in the world [ 16 , 51 , 53 , 54 ]. Indeed, exposure to media is one of the proximal determinants for healthcare information access including the information relevant to the choice of place of delivery.…”
Section: Discussionsupporting
confidence: 88%
“…A global OLS regression was chosen for the analysis of places of childbirth data (Awol & Jemal, 2023) and BCG vaccination among children 0-35 months (Agegnehu, & Alem, 2021) despite findings of spatially clustered service delivery. Linear regression was applied to places of birth data (Gudayu, 2022) despite findings of spatially clustered home births. An analysis by Tusa, Weldesenbet & Kebede (2016) found high incidences of underweight children to be spatially clustered, as did the study of common childhood illnesses and service utilization (Defar, Okwaraji, Tigabu, Persson, & Alemu, 2016).…”
Section: Existing Spatial Analyses Of the Edhs Datamentioning
confidence: 99%
“…An analysis by Tusa, Weldesenbet & Kebede (2016) found high incidences of underweight children to be spatially clustered, as did the study of common childhood illnesses and service utilization (Defar, Okwaraji, Tigabu, Persson, & Alemu, 2016). Determinants of home births were the subject of another study that found significant clustering but relied on OLS for further analysis (Gudayu, 2022). A global OLS regression analysis of drinking water sources was conducted despite the finding that unimproved water sources were spatially clustered (Bogale, 2020).…”
Section: Existing Spatial Analyses Of the Edhs Datamentioning
confidence: 99%